Pembentukan Karakter Kepemimpinan Profetik Berbasis Trilogi Kepemimpinan Ki Hajar Dewantara melalui Kegiatan Kepramukaan - Novi Ariyanti; Unun Zumairoh Asr Himsyah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
This research is motivated by the unique activities of scouts at SMA 45 Purwodadi which are oriented to the formation of leadership characters. The research method used is descriptive qualitative with a case study approach. Through data collection techniques using interviews, observation and documentation, the research seeks to reveal the system used in the formation of leadership character, along with the supporting and inhibiting factors. The results show that the implementation of scouting activities uses the ‘Among’ system which reflects the trilogy values ​​of ‘Ing Ngarso sung Tulodo, Ing madya mangun Karso and Tut wuri Handayani’, meaning that the front gives an example, the middle gives encouragement and the back always encourages. The leadership character is strived to be formed through 5 activities: 1) unit leader rehearsal 2) upgrading, seminars and workshops, 3) Persami 4) Community service camp, and 5) Scout Action Unit (SAKA), so that a prophetic leadership character is formed by increasing knowledge, skills, and abilities. experience and life skills, which adhere to the characteristics of the Prophet, namely ‘Shidiq’, ‘Amanah’, ‘Tabligh’ and ‘Fathanah’. Support and commitment from schools, reliable and experienced scout coaches and synergistic relationships are supporting factors in the formation of leadership characteristics. Meanwhile, student motivation and lack of infrastructure are part of the inhibiting factors that become the material for evaluation and improvement for SMA 45 Purwodadi.